FORMULASI TEPUNG REBUNG BAMBU TIPIS (Dendrocalamus asper) TEPUNG PISANG KEPOK (Musa paradisiaca formatypica) DAN TEPUNG WIKAU MAOMBO TERHADAP KARASTERISTIK PRODUK CRACKERS TINGGI SERAT - Yani, Mohammad Ashabul; Wahyuni, Sri; Sadimantara, Muhammad Syukri (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2020)
ABSTRACTThe purpose of this study was to determine the effect of the thin bamboo shoot (Dendrocalamus asper), Wikau Maombo, and saba banana (Musa paradisiaca formatypica) flours formulation on organoleptic characteristics, proximate value, and antioxidant activity of crackers. This study used a non-factorial completely randomized design using bamboo shoot flour, saba banana flour, and wikau maombo flour (30:20:50), (25:25:50), (20:30:50), (15:35:50), and (10:40:50). Organoleptic assessment data were statistically analyzed using Analysis of Variance (ANOVA). The results of the organoleptic assessment that had a significant effect on the observed variables were further analyzed using Duncan's Multiple Range Test (DMRT) at 95% confidence level (α = 0.01). The results show that the formulation of bamboo shoot flour, saba banana flour, and wikau maombo flour had a very significant effect (P <0.01) on the organoleptic scores of aroma, taste, and texture, while they significantly affected the color parameter. The selected crackers based on the organoleptic assessment was the Y5 formulation (10 g of bamboo shoot flour, 40 g of saba banana flour, and 50 g of wikau maombo flour) with organoleptic assessment scores of color, aroma, taste, and texture reached 2.01 (like), 2.28 (like), 2.11 (like), and 2.17 (like), respectively. The proximate values of the selected crackers products show that it has 3.23% moisture content, 1.54% ash content, 4.69% protein content, 12.39% fat content, 46.60% carbohydrate content, and 13.49% crude fiber content. The results show that the crackers product formulation of thin bamboo shoot flour, saba banana flour, and wikau maombo flour were preferred by the panelists and met the national standards except for protein and carbohydrate contents. The product also had weak antioxidant activity.Keywords: crackers, bamboo shoot flour, saba banana flour, wikau maombo flourABSTRAKTujuan penelitian ini adalah untuk mempelajari pengaruh formulasi tepung rebung bambu tipis (Dendrocalamus asper), tepung Wikau Maombo dan Tepung Pisang Kepok (Musa paradisiaca formatypica) terhadap karakteristik organoleptik, nilai proksimat dan aktivitas antioksidan crackers. Penelitian ini menggunakan Rancangan Acak Lengkap Non Faktorial dengan menggunakan formulasi tepung rebung bambu, tepung pisang kepok dan tepung wikau maombo (30:20:50), (25:25:50), (20:30:50), (15:35:50), (10:40:50). Data hasil penilaian organoleptik dianalisis secara statistik menggunakan Analysis of Varians (ANOVA). Hasil penilaian organoleptik yang berpengaruh nyata terhadap variabel pengamatan, dilanjutkan dengan uji Duncan’s Multiple Range Test (DMRT) pada taraf kepercayaan 95% (α = 0,01). Hasil penelitian menunjukkan bahwa formulasi tepung rebung bambu, tepung pisang kepok dan tepung wikau maombo berpengaruh sangat nyata (P<0,01) terhadap uji organoleptik aroma, rasa dan tekstur, sedangkan pada pada parameter warna berpengaruh nyata. Crackers terpilih berdasarkan penilaian organoleptik terdapat pada formulasi Y5 ( 10 g tepung, rebung bambu, 40 g tepung pisang kepo dan 50 g tepung wikau maombo) dengan skor penilaian terhadap karasteristik organoleptik warna 2,01 (suka), aroma 2,28 (suka), rasa 2,11 (suka) dan tekstur 2,17 (suka). Nilai proksimat dari produk crackers terpilih meliputi: kadar air 3,23%, kadar abu 1,54%, kadar protein 4,69%, kadar lemak 12,39%, kadar karbohidrat 46,60% dan kadar serat kasar 13,49%. Berdasarkan hasil penelitian produk crackers formulasi tepung rebung bambu tipis, tepung pisang kepok dan tepung wikau maombo dapat diterima (disukai) oleh panelis dan telah memenuhi standar SNI terkecuali kadar protein dan kadar karbohidrat serta memiliki aktivitas antioksidan yang lemah.Kata Kunci: crackers, tepung rebung bambu, tepung pisang kepok, tepung wikau maombo